Functional variants in the chromosome 4q21 locus contribute to allergic rhinitis risk by modulating the expression of N‐acylethanolamine acid amidase. Issue 1 (26th April 2021) - Sio, Yang Yie; Shi, Ping; Say, Yee‐How; Chew, Fook Tim
Abstract: Background: Previous haplotype‐based association studies identified chromosome 4q21 as an allergic rhinitis (AR) susceptibility locus; however, the functional role of 4q21 single nucleotide polymorphisms (SNPs) on AR risk remains unclear. Objective: To investigate the functional effect of 4q21 SNPs on AR risk by conducting cohort‐based functional genomics and genetic association analyses. Methods: The associations between 4q21 SNPs and mRNA expression levels of three 4q21‐associated genes ( SDAD1, NAAA and CXCL9 ) in peripheral blood mononuclear cells (PBMCs) were assessed in a Singapore/Malaysia Chinese cohort ( n = 291). Exon expression levels of these genes in PBMCs were tested against the tag‐SNP genotypes in a Singapore Chinese cohort ( n = 30). Serum protein levels of these genes were assessed with tag‐SNP genotypes in a Singapore Chinese cohort ( n = 193). SNP functions were characterized through luciferase assay. In a Singapore Chinese cohort ( n = 1794), we confirmed the associations between functional SNPs and AR. Results: Forty SNPs in 4q21 showed significant associations with NAAA (but not SDAD1 or CXCL9 ) mRNA expression in PBMCs, of which were tagged by two tag‐SNPs, rs17001237 and rs2242470. Both tag‐SNPs rs2242470 and rs12648687 (a proxy for rs17001237) were also significantly associated with the expression level of NAAA exon 1. Tag‐SNP rs12648687 was correlated with serum NAAA level. A four promoter SNPs‐haplotype tagged by rs17001237 influenced the NAAA promoter activity in HEK293T cells. Lastly, individuals carrying the risk allele A of rs12648687 exhibited significantly higher AR risk in the Singapore Chinese population. Conclusions & Clinical Relevance: The rs17001237 linkage set SNPs in the 4q21 locus are associated with NAAA expression at both gene and protein levels ex vivo, have functional consequences in vitro and contribute to AR susceptibility in our study population. Our findings provided a better understanding of the genetic mechanism that contributes to AR pathogenesis. Abstract : 4q21 SNPs are significantly associated with increased NAAA expression in PBMC, increased NAAA level in serum and increased allergic rhinitis risk. Regulation of NAAA expression can be a potential therapeutic target in allergic rhinitis‐affected patients.